Going for Hybrid Crops Breeding in Nepal: Strategies and Policy Dimensions - Tiwari, Khusi Ram; Panthee, Dilip Raj; Joshi, Bal Krishna; Subedi, Kalidas (Nepal Public Policy Review, 2023)
Crop Breeding programs were initiated in Nepal in 1951 with a focus on the varietal improvement of cereal crops. These varieties, however, have limited impact in the farmers' field due to their low adaptation and low yield potentials.  Nepal annually imports hybrid seeds of cereals, vegetables, and flowers from India, China, and elsewhere costing billions of Rupees. It is estimated that approximately 73% of the vegetable seeds and over 60% of the hybrid seeds of maize and rice are imported annually. Hybrid seeds generally produce 20-25% more yield than conventional varieties. Despite this fact, only about 15% of maize and